2013
DOI: 10.1080/13691058.2013.819124
|View full text |Cite
|
Sign up to set email alerts
|

Realigning government action with public health evidence: the legal and policy environment affecting sex work and HIV in Asia

Abstract: The HIV epidemic has shed light on how government regulation of sex work directly affects the health and well-being of sex workers, their families and communities. A review of the public health evidence highlights the need for supportive legal and policy environments, yet criminalisation of sex work remains standard around the world. Emerging evidence, coupled with evolving political ideologies, is increasingly shaping legal environments that promote the rights and health of sex workers but even as new legisla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Our study identified several barriers to health care access among female Ugandan sex workers in Guangzhou. Consistent with studies among sex workers in China [ 26 ], Asian countries [ 27 ], and other countries [ 28 30 ], lack of legal status and a valid visa were key barriers to health service access among women in our study. Fear of being arrested and the perception that hospitals required a valid visa to obtain health care services discouraged women in our study from accessing hospital services.…”
Section: Discussionsupporting
confidence: 88%
“…Our study identified several barriers to health care access among female Ugandan sex workers in Guangzhou. Consistent with studies among sex workers in China [ 26 ], Asian countries [ 27 ], and other countries [ 28 30 ], lack of legal status and a valid visa were key barriers to health service access among women in our study. Fear of being arrested and the perception that hospitals required a valid visa to obtain health care services discouraged women in our study from accessing hospital services.…”
Section: Discussionsupporting
confidence: 88%
“…The criminalisation of some or all aspects of prostitution remains the dominant legal approach globally,1 4 despite growing empirical evidence and clear international guidelines by the WHO, UNAIDS, UNDP and UNFPA calling for full decriminalisation of sex work as necessary to promoting the health and human rights of sex workers (see online supplementary materials for a summary of legal and regulatory responses to sex work).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many international organizations and expert groups, including the World Health Organization and the Global Commission on HIV and the Law, among others, have endorsed the decriminalization of sex work among adults due to the welldocumented harms associated with the criminalization of sex work [1][2][3][4][5]. It has been associated with greater risk of experiencing violence, abuse, discrimination, and increased risk of human immunodeficiency virus (HIV) and other sexually transmitted infections (STIs) among sex workers [1-3, 6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…It has been associated with greater risk of experiencing violence, abuse, discrimination, and increased risk of human immunodeficiency virus (HIV) and other sexually transmitted infections (STIs) among sex workers [1-3, 6, 7]. In areas where sex work is criminalized, street-based sex workers may be displaced to more isolated areas, where they are at an elevated risk of intimidation, violence, theft, and rape, as there are fewer witnesses to protect them [1,[7][8][9][10][11] and they experience a lack of legal protection [8]. When sex workers are more concerned about risk of violence, their ability to negotiate condom use is limited [1,8,10,11], as they must prioritize their immediate safety over risk for infectious disease acquisition [11][12][13].…”
Section: Introductionmentioning
confidence: 99%